-3(3y-10)-y=-4(y-2)

Simple and best practice solution for -3(3y-10)-y=-4(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(3y-10)-y=-4(y-2) equation:



-3(3y-10)-y=-4(y-2)
We move all terms to the left:
-3(3y-10)-y-(-4(y-2))=0
We add all the numbers together, and all the variables
-1y-3(3y-10)-(-4(y-2))=0
We multiply parentheses
-1y-9y-(-4(y-2))+30=0
We calculate terms in parentheses: -(-4(y-2)), so:
-4(y-2)
We multiply parentheses
-4y+8
Back to the equation:
-(-4y+8)
We add all the numbers together, and all the variables
-10y-(-4y+8)+30=0
We get rid of parentheses
-10y+4y-8+30=0
We add all the numbers together, and all the variables
-6y+22=0
We move all terms containing y to the left, all other terms to the right
-6y=-22
y=-22/-6
y=3+2/3

See similar equations:

| -4(5+7v)=7v+15 | | -13-(-14)=x/7 | | -2(2x+3)=-4(x+1)+2 | | 9x4xx=360 | | 12=3/2a-12 | | -1=9=p/8 | | -6x+4(-5x+16)=-92 | | 3x÷20=15;x÷=2 | | 150x+25x=55x | | 5(3c-1)-5=12c+8 | | -6u=-7u-7 | | -6x-9x-14=-2x+2 | | 6x-1-7x=x+5+x | | f=2(-3)^2-3(-3)+1 | | 7x-9=x-45 | | 14y=2(y+5)-2 | | 1/3y−5=1/9y | | 8m^2+14m-9=0 | | 1/3y−5=1/9y. | | 5(3+x)=3(x+3)-4x | | 13y−5=19y. | | 5(3+x)=3(x+3 | | f(5)=10-5 | | 2x-2(1-x)=8x+1 | | 2+y=3(3-y) | | -4.9x^2-1.96x+12=0 | | 8x-48+8=-40 | | 4K+3=(8k+16) | | 2x+9/3=x-9/5 | | 1/4y+3=1/5y | | 14+4z=22 | | 1x÷4=14 |

Equations solver categories